Implementation of Waste Management Policy: Implementasi Kebijakan Pengelolaan Sampah - Muzakki, Ahmad Fikri Alif; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2023)
Implementation of Waste Management Policy at TPA Jabon District, Sidoarjo Regency. Garbage is something that is not used, not used, unpleasant or something that is thrown away that comes from human activities and does not happen by itself. The sources of waste include waste originating from settlements, waste originating from public places, waste originating from offices, waste originating from highways, waste originating from industry (industrial waste), waste originating from/plantations, Garbage originating from mining, waste originating from agriculture and fisheries. Therefore, management is needed to control it so that it does not have a negative impact on public health.This research is a qualitative descriptive approach, with two research locations, the first is the Sidoarjo Environmental and Hygiene Service, and the second is the Final Disposal Site (TPA) in Jabon. The focus of this research is based on the theory of implementation of Edward III with resource persons who can explain the conditions in the field. Data collection techniques were carried out by means of interviews, observation and documentation. The analytical techniques used in this study were collecting data, reducing data, and drawing conclusions.The results showed that the implementation of the Waste Policy at the TPA, Jabon District, Sidoarjo Regency in terms of communication between governments was not optimal due to the lack of commitment from the parties, lack of human resources, optimal disposition and optimal bureaucratic structure.